Prevalence of computer vision syndrome in computer users: a systematic review and meta-analysis - Dimitrijević, Vanja; Todorović, Ivana; Viduka, Biljana; Lavrnić, Igor; Viduka, Dejan (Vojnosanitetski pregled, 2023)
Background/Aim. Vision and health problems associated with the use of computers and other digital devices are known as computer vision syndrome (CVS). Advances in technology have led to increased use of computers, so the prevalence of these symptoms is increasing. The aim of this study was to calculate the overall prevalence of CVS and CVS symptoms using meta-analysis. Methods. The study was developed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement. In July 2021, a systematic search of four electronic databases with article collections was performed: PubMed, Cochrane Library, Web of Science, and Google Scholar. The key search terms were: “computer vision syndrome”, “computer users”, “digital eyestrain”, “headache”, “dry eyes”, “red eyes”, “eyestrain”, “neck pain”, “back pain”, and “shoulder pain”. The articles included in the study had to be original articles written in English only, and the criterion that had to be met was that the research included computer users. As a result, the prevalence of CVS or the prevalence of any of the symptoms of CVS had to be measured. Results. A total of 43 articles were fully reviewed, of which 20 were included in the meta-analysis. The total calculated prevalence for all studies was 74.4%, while the prevalence for individual symptoms was: headache – 43%, dry eyes – 24.4%, eyestrain – 29%, red eyes – 20.7%, and neck, back, or shoulder pain – 46.3%. Conclusion. The results obtained are worrying and point to the necessity of a multidisciplinary approach to solving CVS-related problems.